(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Two types of rapidly solidified ribbons were obtained from the systems Al-Ni-Si and Al-Ni-Si-Cu. By XRD, TEM and DSC analysis the ribbons were proved to be amorphous. By annealing at 350⁰C nanocrystalline alloys were obtained. It was found that when the amorphous alloys are annealed at 190⁰C and 220⁰C, an unknown metastable hexagonal phase is presented, which could not be identified when annealing at 350⁰C is provided. Both studied alloys Al74Ni16Si10 and Al74Ni15Si9Cu9 show that when annealed at 190°C a residual amorphous phase is observed. It is located mainly at the phase boundaries.